RANCANG BANGUN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) PAMEKASAN BERBASIS MAQASHID SYARIAH - Farid Mawardi Sufyan, Akhmad (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2018)
The policy of regional autonomy that came into effect through Law Number 22 and Number 25 of 1999 and was amended by Law Number 32 of 2004 concerning Regional Government and Law Number 33 of 2004 concerning Financial Balance Between Central and Regional brought fundamental changes to all areas of development in the implementation of regional governance and financial relations between the central government and regional governments, with the aim of improving regional autonomy and fiscal decentralization (finance department of the Republic of Indonesia, 2008). Therefore it is important not only to listen to the government's fiscal and monetary policies, but also to design a concept for the regional budget (APBD). thus Designing the Pamekasan regional budget (APBD) based on maqashid sharia is to prioritize the interests of religion, soul, honor, descent and property for the people.